Electrical conductivity and electromagnetic interference shielding effectiveness of nano‐structured carbon assisted poly(methyl methacrylate) nanocomposites. Issue 10 (28th July 2020) - Mondal, Subhadip; Ravindren, Revathy; Shin, Beomsu; Kim, Suhyun; Lee, Hyunsang; Ganguly, Sayan; Das, Narayan Ch.; Nah, Changwoon
Abstract: Nanostructured carbon‐based polymeric nanocomposites are gaining research interest because of their cost‐effectiveness, lightweight, and robust electromagnetic interference (EMI) shielding performance. Till now, it is a great challenge to design and fabricate highly scalable, cost‐effective nanocomposites with superior EMI shielding performance. Herein, highly scalable EMI shielding material with tunable absorbing behaviors comprising of low‐budget ketjen black (K‐CB) reinforced poly(methyl methacrylate) (PMMA) nanocomposites have been prepared using simple solvent assisted solution mixing technique followed by hot compression technique. The morphological investigation revealed the homogeneous distribution of K‐CB and strong interfacial interaction in PMMA matrix, which validated the strong reinforcement and other intriguing properties of the nanocomposites. The PMMA nanocomposites showed a low percolation threshold (2.79 wt%) and excellent electrical conductivity due to the formation of 3D conductive network like architecture within the polymer matrix. Specifically, the 10 wt% K‐CB nanocomposite possessed a superior EMI shielding performance of about 28 dB for X‐band frequency range. Further, a huge change in EMI shielding performance of PMMA nanocomposites is observed with varying thickness. The brand new K‐CB decorated PMMA nanocomposites are expected to open the door for next‐generation cost‐effective EMI shielding materials for academic and industrial applications.